2008
DOI: 10.1086/528787
|View full text |Cite
|
Sign up to set email alerts
|

Radio Submillimeter and γ‐Ray Observations of the 2003 October 28 Solar Flare

Abstract: Radio observations at 210 GHz taken by the Bernese Multibeam Radiometer for KOSMA ( BEMRAK ) are combined with hard X-ray and -ray observations from the SONG instrument on board CORONA-F and the Reuven Ramaty High Energy Solar Spectroscopic Imager (RHESSI ) to investigate high-energy particle acceleration during the energetic solar flare of 2003 October 28. Two distinct components at submillimeter wavelengths are found. The first is a gradual, long-lasting (>30 minutes) component with large apparent source siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 29 publications
4
60
0
Order By: Relevance
“…Figure 4 shows that the optically-thin part of the observed radio spectrum is emitted by electrons in the ∼ 800 to 7,000-10,000 keV energy range, that is above the break energy of the electron spectrum deduced from the HXR/GR photon spectrum. This is consistent with earlier findings (Trottet et al, 1998(Trottet et al, , 2000(Trottet et al, , 2008. B and T trap , which fix the value of N R , are not independent parameters in the data fitting process.…”
Section: Relationship Between Radio and Hxr/gr Emitting Electrons Dursupporting
confidence: 92%
“…Figure 4 shows that the optically-thin part of the observed radio spectrum is emitted by electrons in the ∼ 800 to 7,000-10,000 keV energy range, that is above the break energy of the electron spectrum deduced from the HXR/GR photon spectrum. This is consistent with earlier findings (Trottet et al, 1998(Trottet et al, , 2000(Trottet et al, , 2008. B and T trap , which fix the value of N R , are not independent parameters in the data fitting process.…”
Section: Relationship Between Radio and Hxr/gr Emitting Electrons Dursupporting
confidence: 92%
“…From desirable to have the hard X-ray spectral index at energies up to several hundred keV when making this comparison. Previously, such comparisons between microwave and HXR/γ-ray photon spectra up to several hundreds of keV have been possible with GRANAT/PHEBUS data (Trottet et al 1998;Vilmer et al 1999). Those studies found consistency between the spectral indices of the radio-emitting electrons and the HXR/γ-ray-emitting electrons at energies above several hundred keV.…”
Section: Physical Properties Of Flare-accelerated Particles From Hardmentioning
confidence: 96%
“…One can envisage a source of ultra-relativistic leptons in a very high magnetic field region: Trottet et al (2008) suggest that ultra-relativistic positrons resulting from pion decay are a possible source of the impulsive submillimeter component in SOL2003-10-28T11:10 (X17.2) seen in conjunction with highenergy protons (>200 MeV), although it seems unlikely that sufficient positrons can be produced by this means and energetic electrons are still a more plausible interpretation. An optically-thick thermal source could produce a rising spectrum, but it would have to be either exceptionally large or exceptionally hot (e.g., Silva et al 2007, who prefer an interpretation in terms of gyrosynchrotron emission from electrons in a very strong magnetic field).…”
Section: Sol2002-04-21t01:51 (X15)mentioning
confidence: 99%
“…Indeed, one notices that a pre-increase appeared in the ERNE time profile in the high-energy channels. According to Trottet et al (2008), the acceleration of particles during this solar eruption displays a complex temporal structure, suggesting that several episodes of acceleration occur. Thereby, the pre-increase can result from a different acceleration episode than the one accelerating the particles of the main particle flux.…”
Section: Resultsmentioning
confidence: 99%